Anencefalia e o direito à vida: a decisão do Supremo Tribunal Federal e a separação de poderes - Soares, Vládia Maria de Moura (2016)
This study will have as its main theme the confrontation between the Principle of Human Dignity and Life person, especially when it comes to the case of anencephalic babies. Premature baby's death and the feelings arising from the act of carrying a pregnancy to term without being sure how long it will survive. The technological resources of modern medicine allow early diagnosis, this would have the right to mother therapeutic anticipation of childbirth why are wounded in their dignity to carry a baby with little survival time? The concept of human dignity is central category in the discussion of the right to life and the right to human dignity. We will review the decision of the Supreme Court in holding that the mother does have the power of decision to take or not the pregnancy to term. Can the Supreme Court rule a dilemma like that? Not only would fit the Legislature this rule? The methodology used was the bibliographical research, seeking theoretical basis for authors with knowledge and studies on this topic. The result was a better understanding and knowledge gained from research and can transcribe all material collected and transmit more information to other legal professionals